1073 Sleep Disorders Contribute To Anger In Service Members With Posttraumatic Stress Disorder. (27th May 2020) - Miles, S R; Pruiksma, K; Slavish, D; Nakase-Richardson, R; Nicholson, K; Wardle, S; Young-McCaughan, S; Resick, P; Williamson, D; Dondanville, K; Litz, B; Mintz, J; et al.
Abstract: Introduction: The emotion of anger and behavioral acts of aggression can lead to severe negative consequences, including family violence, legal charges, and death. Anger can be a symptom of posttraumatic stress disorder (PTSD), particularly in service members. Service members report difficulties managing their anger and trouble with the subsequent results. Factors that differentiate service members with PTSD who have anger related problems from those who do not are still unknown. Impaired sleep is associated with negative mood states in the general population and may be a risk factor for anger in those with PTSD. This project examines how sleep disorders commonly diagnosed in service members (i.e., obstructive sleep apnea and insomnia) relate to PTSD and anger. Methods: Ninety-three service members with comorbid PTSD, insomnia, and nightmares (mean age = 35.86 years, SD = 8.38, 27% female, 45% white) completed polysomnography and other measures as part of a clinical trial. A multiple regression model examined how total Apnea Hypopnea Index (AHI), AHI during REM sleep, insomnia (Insomnia Severity Index), age, and race related to PTSD symptoms (Clinical Administered PTSD Scale-5: CAPS-5). A second multiple regression model examined the same variables' associations with anger (Dimensions of Anger Reactions-5; DAR-5). Results: More than a third of the sample (37%) met criteria for OSA (AHI scores > 5) and 99% met criteria for insomnia (ISI > 10). Total AHI and REM AHI were not associated with CAPS-5 scores or ISI. Across OSA and PSG indices, only greater REM AHI (b=.07, p<.05) and Insomnia (b=.43, p<.05) were positively associated with DAR-5 anger scores. Total AHI was unrelated to anger. Conclusion: Elevated REM AHI and insomnia were associated with greater anger in service members with PTSD. Current treatments for anger are only moderately effective. Assessing and treating comorbid sleep disorders may reduce anger and enhance successful PTSD treatment. Support: Consortium to Alleviate PTSD (W81XWH-13-2-0065), DVA (I01CX001136-01), GDHS (W91YTZ-13-C-0015) for DVBIC.